Trichotemnomania in an Adolescent Girl: A Case Report of an Asian Child and Literature Review - V. Thadchanamoorthy; Markandu Thirukumar; Kavinda Dayasiri; N. Thamilvannan; Judy Jeyakumar (Hindawi Limited, 2020)
Trichotemnomania (TT) refers to cutting or shaving of one's own hair as a compulsive act. This condition is reported rarely and may be indicative of an underlying obsessive-compulsive disorder. TT may be misdiagnosed with trichotillomania or other disorders such as alopecia areata, tinea capitis, and postinflammatory scars. The diagnosis of trichotemnomania is confirmed by dermoscopic assessment, histopathological changes of hair, and correlation of these findings with clinical history. A fourteen-year-old adolescent girl presented with focal hair loss over forehead for duration of two-weeks and periodic abnormal breathing and poor sleep for 2-month duration. Besides, she had also lost some of pubic hair and hair on the forearm over preceding 24 hours. This patient was assessed by a team including a paediatrician, gynecologist, dermatologist, and psychiatrist to gather focused medical history and to perform physical examination, laboratory investigations, and dermoscopic assessment. It was revealed that she used to shave or cut regularly following stressful situations across various aspects of her life and hyperventilate as a means of relieving her stress. Eventually, she was diagnosed to have trichotemnomania and was started oral sertraline 50 mg/day for one month. Clinical features and her behaviour improved with regular cognitive behavioural therapy, and hairs were demonstrated to grow up normally with change in behaviour. Currently, she does well at school and is off medications and being followed up at the child guidance clinic. Trichotemnomania is a very rare disorder which is characterised by cutting or shaving of one's own hairs as a compulsive habit. The condition needs careful and detailed assessment by a team of specialists to identify coexisting psychiatric disorders and offer treatment.